Investment in R&D and Corporate Governance - Valdemar Smith; Erik Strøjer Madsen (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
The paper investigates the impact of ownership concentration on the likelihood that firms are involved in innovative activities or invest in research and development. We find that more dispersed ownership significantly increases the probability that a firm is engaged in innovation or invests in research and development. Moreover, the effect from ownership concentration is far more important for the incentive to innovate than the effect from product market concentration.
Keywords: 330; Industrieforschung; Innovation; Investition; Eigentümerstruktur; Corporate Governance; Schätzung; Dänemark